2019
DOI: 10.3390/antiox8120622
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative Defense and Fertility Rate in the Assessment of Reprotoxicity Risk Posed by Global Warming

Abstract: The objective of this review is to briefly summarize the recent progress in studies done on the assessment of reprotoxicity risk posed by global warming for the foundation of strategic tool in ecosystem-based adaptation. The selected animal data analysis that was used in this paper focuses on antioxidative markers and fertility rate estimated over the period 2000–2019. We followed a phylogenetic methodology in order to report data on a panel of selected organisms that show dangerous effects. The oxidative dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 136 publications
1
22
0
Order By: Relevance
“…Continuous effort has been made to assess the role of antioxidants in reproductive health and fertility rate under the risk of global warming [68]. In the present study, it is concluded that melatonin administration throughout pregnancy leads to the improvement of the redox status in heat-stressed ewes, as well as the pregnancy rate, number of lambs born, and milk yield during puerperium.…”
Section: Discussionmentioning
confidence: 57%
“…Continuous effort has been made to assess the role of antioxidants in reproductive health and fertility rate under the risk of global warming [68]. In the present study, it is concluded that melatonin administration throughout pregnancy leads to the improvement of the redox status in heat-stressed ewes, as well as the pregnancy rate, number of lambs born, and milk yield during puerperium.…”
Section: Discussionmentioning
confidence: 57%
“…Heavy metals accumulation in fish has potentiality to induce toxicological effects [1,2] and cause oxidative damage to tissues determining cell functions loss [10,11,56]. Cu and Zn inhibit a number of enzymes, it follows that the basis for their toxicity may be due to their diminished activity.…”
Section: Discussionmentioning
confidence: 99%
“…At transcriptional levels, SOD, CAT, GPx and GST gene expression pattern have been validated as biomarkers of exposure to oxidative stress-inducing chemical pollutants and also to abiotic factors such as hyperthermia [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations